PEMBELAJARAN TAHSIN PADA TAMAN PENDIDIKAN AL-QURAN (TPA) DI KECAMATAN AMUNTAI SELATAN KABUPATEN HULU SUNGAI UTARA: Studi Kasus pada TPA Nurul Huda Desa Padang Tanggul, TPA Nurul Iman Desa Harusan Telaga dan TPA Al-Muhibbin Desa Telaga Silaba - Hamli, Hamli; Purnamasari, S (Asosiasi Dosen PTKIS Indonesia, 2021)
Abstract:. This research is learning tahsin at the Al-Qur'an Education Park (TPA) in Amuntai Selatan District, Hulu Sungai Utara Regency. This research departs from the author's initial observation that there are already many students who have met the standards/rules of reading the al-Qur'an. Based on this, the objectives raised in this study were to determine the learning of tahsin at the Al-Qur'an Education Park (TPA) in Amuntai Selatan District, Hulu Sungai Utara Regency which includes the accuracy of letter makhrojul, accuracy of tajwid, tartil, and fluency. Sources of data in this research are students who study at TPA Nurul Huda, Padang Tanggul Village, TPA Nurul Iman Harusan Telaga Village and TPA Al-Muhibbin Telaga Silaba Village. The data collection technique was done by means of observation, interview and documentation. Data analysis techniques used data reduction, data display, and data verification. The results of this study indicate that learning tahsin in the Al-Qur'an Education Park (TPA) in Amuntai Selatan District Hulu Sungai Utara Regency includes; 1) Accuracy of Letter Macrojul. On average, children / students who study at TPA Nurul Huda, Padang Tanggul Village, Nurul Iman TPA Harusan Telaga Village and Al-Muhibbin TPA Telaga Silaba Village are able to pronounce letter macros correctly and correctly. The child/student is fluent in pronouncing it letter by letter. 2) The accuracy of the Tajweed. On average, children/students who study at TPA Nurul Huda, Padang Tanggul Village, TPA Nurul Iman Harusan Telaga Village and TPA Al-Muhibbin Telaga Silaba Village are able to read the al-Qur'an by way of tajwid. Many of these children/tudents already know the laws in reading the Qur'an, such as the law of idzhar, idgham bi ghunnah, idgham if ghunnah, ikhfa, qalqalah, iqlab, and mad. 3) Tartil. On average, children/students who study at TPA Nurul Huda, Padang Tanggul Village, TPA Nurul Iman Harusan Telaga Village and TPA Al-Muhibbin Telaga Silaba Village are able to read the al-Qur'an by tartil. These children/students do not read the Qur'an in the way they like. The point is the way children/students read the al-Qur'an with songs in a regular manner. 4) Smoothness. On average, children/students who study at TPA Nurul Huda, Padang Tanggul Village, Nurul Iman TPA Harusan Telaga Village and TPA Al-Muhibbin Telaga Silaba Village are fluent in reading the al-Qur'an. The children/students are not intermittent, choked up, procrastinated in reading the al-Qur'an.